Human Resource Management as a Corporate Profession - ZHAO, Lingling (IJRDO - Journal of Business Management, 2017)
The aim of this paper is to distinguish human resource management (HRM) as a new corporate profession following detailed definitions of related concepts on professionalization. The methodology adopted in this thesis is documentation analysis from literature review. It can be divided into three sections. First, it introduces the background and development of professions. Second, it provides an overview of the key terminology used throughout the thesis, including the key concepts of professions, professionals and professionalization. Third, it examines the notion of corporate professions, which is as an emerging trend in the field and to which HRM currently belongs. Finally, it concludes contents discussed in this research and its implications to research in HRM field.